Photoshop CS3 bible - Ulrich-Fuller, Laurie 1961- (Wiley Pub., 2007)
Provides instructions on using Adobe Photoshop CS3, covering such topics as image management, painting and retouching, filtering, masks, distortions and effects, layers, mapping colors, and printing and publishing.
Title from title screen. - Includes index and link to CD content
Keywords: Adobe Photoshop; Photography -- Digital techniques; Computer graphics; Computer Graphics; Photography -- methods; Adobe Photoshop (Computer software); Photographie numérique; Infographie; computer graphics; COMPUTERS; Computer Graphics; Image processing; Digital techniques; Computer drawing; Photography; Digital techniques